The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/annrheumdis-2020-217208
|View full text |Cite
|
Sign up to set email alerts
|

MRI of sacroiliac joints for the diagnosis of axial SpA: prevalence of inflammatory and structural lesions in nulliparous, early postpartum and late postpartum women

Abstract: ObjectivesTo determine the prevalence of bone marrow oedema (BME) at the sacroiliac joint (SIJ) in early postpartum (EPP), nulliparous (NP) and late postpartum (LPP) women, and to identify factors associated with BME presence at the SIJ.MethodsThree groups were obtained: NP (never given birth), EPP (given birth within 12 months) and LPP (given birth more than 24 months). The primary outcome was the presence of BME and/or structural lesions (erosions, osteophytes, ankylosis and sclerosis) at the SIJ MRI.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 22 publications
6
24
0
1
Order By: Relevance
“…Subchondral sclerosis occurred more frequently and was more pronounced in non-SpA patients with childbirth history (64%; average total depth 4.0 mm) compared to non-SpA patients without childbirth history (40%; average total depth 2.1 mm), which is consistent with the findings in other publications [6,14,16]. Interestingly, our study showed no differences in regard to sclerosis score or sclerosis depth between non-SpA patients with childbirth and SpA patients without childbirth, whereas significant differences prevailed between non-SpA patients with childbirth and SpA patients with childbirth.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Subchondral sclerosis occurred more frequently and was more pronounced in non-SpA patients with childbirth history (64%; average total depth 4.0 mm) compared to non-SpA patients without childbirth history (40%; average total depth 2.1 mm), which is consistent with the findings in other publications [6,14,16]. Interestingly, our study showed no differences in regard to sclerosis score or sclerosis depth between non-SpA patients with childbirth and SpA patients without childbirth, whereas significant differences prevailed between non-SpA patients with childbirth and SpA patients with childbirth.…”
Section: Discussionsupporting
confidence: 91%
“…In our cohort, pregnancy/ childbirth yielded no significant effect on BME score. This indicates that the well-known effect of pregnancy/childbirth on SIJ regarding BME in the early postpartum period [9-11, 14, 16] will vanish with time, which is consistent with findings of a recent study by Hoballah et al, comparing women without childbirth history with women in either the early (first postpartum year) or late postpartum period (≥ 2 years after delivery) [16]. We found no association between either age, time after last childbirth, birth method, or number of children and BME score in our cohort.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…2 In fact, the presence of Crohn's disease or ulcerative colitis is part of the Assessment of SpondyloArthritis international Society criteria for the diagnosis of ax-SpA. 3 In our study, on the prevalence of bone marrow oedema (BME) at the sacroiliac joint (SIJ) in postpartum women, 4 we excluded those with known risk factors for developing ax-SpA, such as family or patient history of inflammatory diseases. The exclusion of women with known risk factors for developing ax-SpA was deemed important to eliminate potential confounding factors, and hence ascertain whether observations of sacroiliitis were triggered by, or related to, pregnancy and childbirth as opposed to other aetiologies.…”
mentioning
confidence: 99%